Ampullary adenocarcinoma: Defining predictors of survival and the impact of adjuvant therapy following surgical resection for stage I disease. Issue 7 (8th March 2018) - Stiles, Zachary E.; Behrman, Stephen W.; Deneve, Jeremiah L.; Glazer, Evan S.; Dong, Lei; Wan, Jim Y.; Martin, Michael G.; Dickson, Paxton V.
Abstract : Background and Objectives: Outcomes and recommendations regarding adjuvant therapy (AT) for stage I ampullary adenocarcinoma (AAC) are inadequately described. We sought to determine factors associated with survival and better define the impact of AT. Methods: The NCDB was queried for stage I AAC patients undergoing resection. We evaluated variables influencing the administration of AT and affecting survival, including the receipt of AT. Results: Five hundred thirty‐seven patients were identified. 1, 3, and 5‐year OS were 91.3%, 78.8%, and 67.4%, respectively. 103 received AT: 101 chemotherapy, 31 radiation, and 29 a combination of both. AT was more commonly utilized in patients with poorly differentiated and T2 tumors. Comorbid disease was inversely associated with use of AT. Age ≥65 was associated with decreased survival for stage IA and IB, while positive resection margins and sampling of <12 LNs were associated with decreased OS for stage IA and IB, respectively. After propensity matching key covariates, no significant difference in OS was observed between those receiving and not receiving AT ( P = 0.449). Conclusion: This analysis revealed a modest 5‐year OS for stage I AAC. Age, positive resection margins, and evaluation of <12 LNs negatively influenced OS and AT did not convey a survival benefit.